Prognostic value of myocardial salvage index assessed by cardiovascular magnetic resonance in reperfused ST-segment elevation myocardial infarction - Zhang, Shiru; Ma, Quanmei; Jiao, Yundi; Wu, Jiake; Yu, Tongtong; Hou, Yang; Sun, Zhijun; Zheng, Liqiang; Sun, Zhaoqing (Frontiers in Cardiovascular Medicine, 2022)
AIMS: Cardiovascular magnetic resonance (CMR) is a powerful tool to quantify the myocardial area at risk and infarct size, and evaluate extent of myocardial salvage in acute ST-segment elevation myocardial infarction (STEMI). This study aimed to assess the prognostic value of myocardial salvage index (MSI) assessed by CMR in reperfused STEMI and investigate whether MSI could improve the predictive efficacy of the Global Registry of Acute Coronary Events (GRACE) risk score. METHODS AND RESULTS: 104 consecutive patients who were hospitalized with first-time STEMI and received reperfusion therapy were prospectively enrolled. The primary endpoint was the incident major adverse cardiovascular event (MACE) including all-cause mortality, nonfatal myocardial reinfarction and congestive heart failure within 36 months after the index event. Cox regression analysis were used to evaluate the prognostic association of MSI with MACE risk. 21(20.2%) patients developed MACE during the 3-year follow-up period, and patients with MSI < median had a higher incidence of MACE than those with MSI ≥ median (16[30.8%] vs. 5[9.6%], P=0.007). After adjusting all the parameters associated with MACE in univariate Cox analysis, MSI assessed by CMR remained independently significant as a predictor of MACE in multivariate Cox analysis (hazard ratio 0.963, 95% CI: 0.943-0.983; P＜0.001). Adding MSI to Global Registry of Acute Coronary Events (GRACE) risk score significantly increased prognostic accuracy of GRACE risk score (area under the curve: 0.833 vs. 0.773; P=0.044), with a net reclassification improvement of 0.635 (P=0.009) and an integrated discrimination improvement of 0.101 (P=0.002). CONCLUSION: This study confirmed that MSI assessed by CMR had a good long-term prognostic value in reperfused STEMI and improve the prognostic performance of GRACE risk score.